Dementia in the older population is associated with neocortex content of serum amyloid P component. Issue 4 (9th October 2021) - Ellmerich, Stephan; Taylor, Graham W; Richardson, Connor D; Minett, Thais; Schmidt, Amand Floriaan; Brayne, Carol; Matthews, Fiona E; Ince, Paul G; Wharton, Stephen B; Pepys, Mark B; ,
Abstract: Despite many reported associations, the direct cause of neurodegeneration responsible for cognitive loss in Alzheimer's disease and some other common dementias is not known. The normal human plasma protein, serum amyloid P component, a constituent of all human fibrillar amyloid deposits and present on most neurofibrillary tangles, is cytotoxic for cerebral neurones in vitro and in experimental animals in vivo . The neocortical content of serum amyloid P component was immunoassayed in 157 subjects aged 65 or more with known dementia status at death, in the large scale, population-representative, brain donor cohort of the Cognitive Function and Ageing Study, which avoids the biases inherent in studies of predefined clinico-pathological groups. The serum amyloid P component values were significantly higher in individuals with dementia, independent of serum albumin content measured as a control for plasma in the cortex samples. The odds ratio for dementia at death in the high serum amyloid P component tertile was 5.24 (95% confidence interval 1.79–15.29) and was independent of Braak tangle stages and Thal amyloid-β phases of neuropathological severity. The strong and specific association of higher brain content of serum amyloid P component with dementia, independent of neuropathology, is consistent with a pathogenetic role in dementia. Abstract : The normal blood protein, serum amyloid P component (SAP), is toxic for cerebral neurones but normally is largely excluded from the brain. Ellmerich et al. report that higher neocortical content of SAP is strongly associated with dementia at death, consistent with a pathogenetic role of SAP in neurodegeneration. Graphical Abstract: